Association Between Colorectal Cancer Susceptibility Loci and Survival Time After Diagnosis With Colorectal Cancer - Phipps, Amanda I. (2012)
Genome-wide association studies have identified 16 germline single-nucleotide polymorphisms (SNPs) that are associated with colorectal cancer (CRC) incidence. We examined the relationship between these SNPs and survival of 2611 individuals with CRC, enrolled in 5 cohort studies. We used Cox regression analysis to associate SNPs with overall and CRC-specific survival times. The minor allele in rs4939827 (SMAD7) was associated with reduced overall survival (hazard ratio, 1.16; 95% confidence interval, 1.06–1.27; P = .002) and disease-specific survival (hazard ratio, 1.17; 95% confidence interval, 1.05–1.30; P = .005). Other SNPs were not associated significantly with survival. Common germline variations might be prognostic factors for patients with CRC. A variant in SMAD7 could affect progression of CRC.